A comparative assessment of the challenges of prosecuting rape offences in Nigeria and India - Dimas, Appolos (African journal of law and criminology, 2024)
This work examined the challenges in the prosecution of the offence of rape in Nigeria and India. The objectives of the work among others are to evaluate the legal framework for the trial of the offence of rape in Nigeria and India and the challenges encountered in the prosecution of the offence. In doing so, the research examined the extant laws on the offence of rape in Nigeria and India and brought out the loopholes in these laws. The study also determined why it is always difficult to secure a conviction in courts despite the availability of laws and overwhelming evidence against perpetrators. The method used in this research was doctrinal and it involved the analysis and review of statutes, regulations, case laws and other secondary materials such as textbooks, journals, and internet materials were also consulted. The findings of the research reveals that there is a need to have a broader definition that will encompass the various forms of rape that are committed through other mediums other than the traditional penetration of the vagina by the penis. The research ended with a conclusion and recommendations.